(untitled) - Asian Simulation Conference (New York, 2005)
This book constitutes the refereed post-proceedings of the third Asian Simulation Conference, AsiaSim 2004, held in Jeju Island, Korea in October 2004. The 78 revised full papers presented together with 2 invited keynote papers were carefully reviewed and selected from 178 submissions; after the conference, the papers went through another round of revision. The papers are organized in topical sections on modeling and simulation methodology, manufacturing, aerospace simulation, military simulation, medical simulation, general applications, network simulation and modeling, e-business simulation, numerical simulation, traffic simulation, transportation, virtual reality, engineering applications, and DEVS modeling and simulation.
Keywords: Computer simulation,Flexible manufacturing systems,Mô phỏng bằng máy tính,Hệ thống sản xuất linh hoạt; Computer simulation,Mô phỏng bằng máy tính